Progesterone, prolactin, and gynaecomastia in men with liver disease. Issue 4 (April 1982) - Farthing, M J; Green, J R; Edwards, C R; Dawson, A M
Abstract : Plasma progesterone was raised in 36 of 50 (72%) men with liver disease compared with 20 healthy male control subjects. Plasma progesterone was significantly higher in men with non-alcoholic cirrhosis with gynaecomastia than those without, but no similar relationship was found in men with alcoholic fatty change and alcoholic cirrhosis. Hyperprolactinaemia was found in 14% of men with liver disease but levels were unrelated to the presence of gynaecomastia. Increased circulating levels of progesterone and prolactin alone do not explain the development of gynaecomastia in patients with liver disease, but progesterone may be an additional factor acting in association with the known disturbances of other sex steroids.